Звичаї життєвого циклу сербів у Каліфорнії (США) - Благоєвич, Г. (Народна творчість та етнологія, 2012)
Gordana Blagojewich. Life Cycle Folkways of the Serbs in California (USA). The American way of life influences to a considerable extent the life cycle folkways (baptism, wedding, monasticism, funeral rituals) of the Serbs in California. The ceremony of baptizing adults is carried out either in church or in pools within private homes or condominiums. The weddings in most cases take place on Saturdays and are preceded by a “general rehearsal” in church, where the participants practice the wedding arrangements. The funeral rites have been affected by US laws, from the “beautification” of the deceased to the funeral time schedule, to tombstone height. The Americanization of the people of faith is shaping, so to speak, the “Americanization” of the ritual-religious practices.